PEMBUATAN ARANG AKTIF DARI KAYU ACACIA MANGIUM DENGAN GASIFIKASI "FLUIDIZED BED" - Djeni Hendra; Gustan Pari (Jurnal Penelitian Hasil Hutan, 1995)
Experimental study on activated charcoal from Acacia mangium by using "fluidized bed" gasification is presented in this paper. Tire result shows that yield ranges from 14. 79 to 25. 03 %, moisture content from 9.17 to 14.42 %, ash content from 2.36 to 2.94, volatile matter from 7.44 to 9. 79 %, fixed carbon from 73.28 to 80. 71 %. adsorptive capacity of benzene from 1.38 to 18.56 % and adsorptive iodine from 511.37 to 961.87 %.Based on adsorptive capacity of iodine, the maximum activation reaction time is 45 minutes. At this time the adsorptive of iodine is 961.87 which meet American and Indonesian standard.